The Juridical Review of Making a Marriage Agreement Deed Based on a Decision of the Jepara District Court - Rahmawati, Dewi (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2022)
The implication of the Constitutional Court Decision Number 69/PUU-XIII/2015 on the making of a marriage agreement deed after marriage made before a Notary changes the legal mechanism for making a marriage agreement. On a scientific basis, writing is motivated to carry out a scientific study in the form of systematic and fundamental research with the title